PELATIHAN DAN PENYULUHAN PADA MASYARAKAT TENTANG PEMBUATAN KOMPOS KASCING (BEKAS KOTORAN CACING) DI DESA CANDI - Sulistyaningsih (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
This community service aims to improve the skills of the people of Candi village to utilize worm droppings by making compost and developing their skills independently, so that they can produce, pack and put label as well as to market Kompos Kascing (worms compost) as additional income. The method of implementing this activity is the Training and practice on how to make the Compost of Kompos Kascing. Outcomes of the community service program in the form of: compost products, Packaging and labeling. Through this activity the results can be utilized by the surrounding community and marketed online.